Analysis of Design Change Management in a Construction Project at Jl. Duta Permai 2 No. 6, Pondok Indah: Case of Owner Mr. Patrick - Muhammad Malik Abdul Jabbar; Era Agita Kabdiyono (International Journal Science and Technology, 2025)
Design changes in construction projects often pose significant challenges, impacting the cost, quality, and timeline of the projects. This study aims to analyze the management of design changes in a construction project located at Jl. Duta Permai 2 No. 6, Pondok Indah, with a focus on identifying the causes, the management strategies implemented, and their overall impact on the project. The research employs a qualitative descriptive method, collecting data through interviews, observations, and analysis of relevant documents. The findings indicate that the primary factors causing design changes include regulatory changes, owner requests, and technical constraints that arise during construction execution. The management strategies applied by the project team, while systematic, still face challenges in communication that can hinder decision-making. The results reveal that poorly managed design changes can lead to project delays and cost increases of up to 20%. This study recommends enhancing communication among stakeholders and providing training on change management to minimize the impacts of design changes in the future. Through this analysis, it is expected to provide insights and references for project managers and future researchers in managing design changes more effectively